The Influence of Brand Image, Brand Awareness and Lifestyle on Intention In Buying Lanccelot Watch Products in Karawang - Sunarya, Asep; Hersona, Sonny; Jajang, Dede (Islamic University of Kalimantan MAB Banjarmasin, 2025)
This research aims to determine the influence of brand awareness, brand image and lifestyle on buying intention in Lanccelot watch products in Karawang. This research uses quantitative research with hypothesis testing. The sample used in this research was 100 Lanccelot watch consumers in Karawang. The analytical tools used in this research are multiple linear regression analysis, coefficient of determination (R2), partial correlation coefficient, t test, f test, and classical assumption test using SPSS version 20 statistical software. The main data in this research comes from a questionnaire. The results of this research prove that brand awareness influences intention in purchasing Lanccelot watch products in Karawang. Brand image influences intention in purchasing Lanccelot watch products in Karawang. Likewise, lifestyle influences intention in buying Lanccelot watch products in Karawang. Brand awareness, brand image and lifestyle simultaneously influence intention in purchasing Lanccelot watch products in Karawang.